2007
DOI: 10.1142/s0192415x07005272
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective and Antioxidant Effects of Ethanol Extract fromPhellinus merrilliion Carbon Tetrachloride-Induced Liver Damage

Abstract: In the present study, we investigated the hepatoprotective and antioxidant capacities of ethanol extract of Phellinus merrillii (PM) on carbon tetrachloride-induced hepatotoxicity. In high-performance liquid chromatography (HPLC) analysis, the finger print chromatogram of PM was established. Both hispolon and PM showed a similar peak at the retention time of 6 min. This implied that PM did contain the active ingredient of hispolon. Treatment with PM (0.5, 1 and 2 g/kg) prior to the administration of carbon tet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 35 publications
2
20
0
Order By: Relevance
“…And we also found that hispolon, a phenolic compound from Phellinus merrillii , exhibited antioxidant activity. Phenolic compounds possess antioxidant, radical scavenging, and antimutagenic and anticarcinogenic properties [21]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…And we also found that hispolon, a phenolic compound from Phellinus merrillii , exhibited antioxidant activity. Phenolic compounds possess antioxidant, radical scavenging, and antimutagenic and anticarcinogenic properties [21]. …”
Section: Discussionmentioning
confidence: 99%
“…Many studies have demonstrated that antioxidant enzymes such as SOD, CAT, and GPx represent one protection against oxidative tissue damage [21]. SOD is an effective defense enzyme that converts the dismutation of superoxide anions into hydrogen peroxide (H 2 O 2 ) [22].…”
Section: Discussionmentioning
confidence: 99%
“…Many factors such as solvent characteristic, extraction time, temperature, and ratio of sample to solvent have an influence on extraction 11 . In this experiment, we selected ethanol as a solvent followed the work of Chen et al 8 because the crude extract of PL contains effective component in an anti-cancer test. Our extraction results showed that the hispolon contents at 4 h of extraction time with 50%, 80%, and 95% ethanol were 0.0000 mg/g, 0.0025 mg/g, and 0.0147 mg/g of dried mushroom powder, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Various aromatic hydrocarbons including caffeic acid, hydroxybenzaldehyde, hispidin, hispolon, and inotilone have also been characterized from the mycelium extracts and exhibited significant antioxidant and anti-inflammatory activities [ 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. Recently, several articles reported the hepatoprotective and antihepatotoxic effects of the Phellinus genus [ 28 , 29 , 30 , 31 , 32 ]. In our preliminary study, the ethanol extract of cultured mycelium of P. linteus (PLE) exhibited protective effect against hepatic fibrosis in experimental animals.…”
Section: Introductionmentioning
confidence: 99%